LAJU ADSORPSI DAN DESORPSI PARAQUAT PADA TANAH PERTANIAN DESA OESAO KECAMATAN KUPANG TIMUR - Sherlly M.F. Ledoh; Hermania Em Wogo; Siti Arianti S.A (Molekul, 2010)
The research about determination of kinetic adsorption and desorption rate of paraquat on agriculture area Oesao-east Kupang has been done. The aim of this research was to determine the kinetic of paraquat adsorption before and after saturated and to model the desorption. The research consisted of evaluation of the analitycal procedure for paraquat, pattern of soil kinetic adsorption and paraquat desorption. The result of procedure evaluation showed that reduced paraquat absorbed at λ maximum 606 nm and relative stability at 0-150 minutes. Constant of paraquat kinetic adsorption at natural state bigger than saturated state. k1 value at natural state was 0,011 per minute whereas k1 value at saturated state was 0,003 per minute. Desorption model of paraquat by using three desorbents were ammonium chloride, 29,2% of sea water salinity and aquadest showed the best desorbent was ammonium chloride, followed by sea water and aquadest.